CORRELATION BETWEEN POLITICAL DISTRUST AND ATTITUDE TOWARDS GOVERNMENT CREDIT FACILITIES AMONG SMALL-HOLDER FARMERS IN ENUGU STATE, NIGERIA - Anochili, Cuthbert I. (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
The present paper examined political distrust as a factor that could correlate with smallholder farmers' attitudes toward accessing government credit facilities. As the study's participants, two hundred and six (n=206) smallholder farmers were conveniently pooled from different locations in Enugu states. A correlation research design was employed in the present paper. The data collected with the instrument were analyzed using the statistical package for social sciences (SPSS, Version 23). A Pearson's product-moment correlation was computed to determine the correlation between political mistrust and smallholder farmers' attitudes towards accessing government credit. The analyses revealed that the relationship is linear. Indeed, both variables were normally distributed, as observed in the Shapiro-Wilk test (p > .05). Also, there were no outliers. However, the analysis showed a statistically significant positive correlation between political mistrust and smallholder farmers' attitudes towards accessing government credit, r (204) = .46, p < .001. Most importantly, the R2 indicated that political mistrust explained about 21.2% of the variation in smallholder farmers' attitudes towards accessing government credit facilities in Southeast Nigeria. The result has implications for research and food production.